Three years in California [1851-54] - Borthwick, John David (Edinburgh, London, W. Blackwood and sons, 1857)
Edinburgh-born artist John David Borthwick (1825-c.1900) left New York for California in 1851, crossing the Isthmus at Chagres. In 1860 Borthwick returned to Britain, where his paintings were exhibited in several galleries including the Royal Academy. Three years in California (1857) focuses on his experiences mining gold and quartz at Hangtown, Foster's Bar, Downieville, Mississippi Bar, Jacksonville, and Carson's Hill. He devotes much attention to social life in the camps as well as mining techniques, describing crime, the Chinese and French and other ethnic groups, and holidays and public entertainments. Borthwick illustrated the book with eight of his own lithographs which are considered the most realistic of the period for California.
Not by John Douglas Borthwick of Montreal, Can.
Also available in digital form on the Library of Congress Web site.
Keywords: California -- Gold discoveries; California -- Social life and customs; Ethnic groups -- California; Law -- Political aspects -- California